High-fat diet induces depression-like behaviour in mice associated with changes in microbiome, neuropeptide Y, and brain metabolome. (2nd December 2019) - Hassan, Ahmed M.; Mancano, Giulia; Kashofer, Karl; Fröhlich, Esther E.; Matak, Andrija; Mayerhofer, Raphaela; Reichmann, Florian; Olivares, Marta; Neyrinck, Audrey M.; Delzenne, Nathalie M.; Claus, Sandrine P.; Holzer, Peter
Abstract : Objectives: The biological mechanisms linking diet-related obesity and depression remain unclear. Therefore, we examined the impact of high-fat diet (HFD) on murine behaviour, intestinal microbiome, brain metabolome, neuropeptide Y (NPY) expression, and dipeptidyl peptidase-4 (DPP-4) activity. Methods: Male C57Bl/6J mice were fed an HFD (60 kJ% from fat) or control diet (12 kJ% from fat) for 8 weeks, followed by behavioural phenotyping. Caecal microbiome was analysed by 16S rDNA sequencing, brain metabolome by 1 H nuclear magnetic resonance, NPY expression by PCR and immunoassay, and dipeptidyl peptidase-4 (DPP-4) activity by enzymatic assay. The effect of a 4-week treatment with imipramine (7 mg/kg/day) and the DPP-4 inhibitor sitagliptin (50 mg/kg/day) on HFD-induced behavioural changes was also tested. Results: HFD led to a depression-like phenotype as revealed by reduced sociability and sucrose preference. In the caecum, HFD diminished the relative abundance of Bacteroidetes and increased the relative abundance of Firmicutes and Cyanobacteria. In the brain, HFD modified the metabolome of prefrontal cortex and striatum, changing the relative concentrations of molecules involved in energy metabolism (e.g. lactate) and neuronal signalling (e.g. γ-aminobutyric acid). The expression of NPY in hypothalamus and hippocampus was decreased by HFD, whereas plasma NPY and DPP-4-like activity were increased. The HFD-induced anhedonia remained unaltered by imipramine and sitagliptin. Discussion: The depression-like behaviour induced by prolonged HFD in mice is associated with distinct alterations of intestinal microbiome, brain metabolome, NPY system, and DPP-4-like activity. Importantly, the HFD-evoked behavioural disturbance remains unaltered by DPP-4 inhibition and antidepressant treatment with imipramine.